Use Algebra of Group Action to Find Special Types of Caps in PG(3,13) - Attook, Saja Makki; Al-Zangana, Emad Bakr (Iraqi Journal of Science, 2023)
Group action on the projective space PG(3,q) is a method which can be used to construct some geometric objects for example cap. We constructed new caps in PG(3,13) of degrees 2, 3, 4, 7,14 and sizes 2, 4, 5, 7, 10, 14, 17, 20, 28, 34, 35, 68, 70, 85, 119, 140, 170, 238, 340, 476, 595, 1190. Then the incomplete caps are extended to complete caps.